INCREASING TEACHERS' ABILITY USING ZOOM MEETING APPLICATIONS IN THE DISTANCE LEARNING PROCESS THROUGH COLLABORATIVE ASSISTANCE IN SD NEGERI BENDO KAPANEWON SAMIGALUH KULON PROGO ACADEMIC YEAR 2020/2021 - Francisca Saminem (International Journal of Chemistry Education Research, 2021)
This research was motivated by the regulation of the Ministry of Education and culture regarding the implementation of education during the Covid-19 pandemic which required distance learning using online learning media. Online learning is a learning method that aims to improve the ability of teachers to use the Zoom Meeting application program at SD Negeri Bendo Kapanewon, Samigaluh Kulon Progo during the Covid-19 pandemic. This research is a school action research to improve the ability of school principals in managing learning leadership through collaborative mentoring. The subjects in this study were SD Negeri Bendo teachers, totaling 8 teachers consisting of 6 classroom teachers and 2 subject teachers. The purpose of this study was to improve the ability of teachers in implementing distance learning by using the Zoom Meeting application for Bendo Elementary School teachers through collaborative mentoring activities. The results of preliminary observations show that the ability of teachers at SD Bendo Kapenewon, Samigaluh, Kulon Progo, using the Zoom Meeting application is still in the "Not Good" category with a percentage reaching 87.50%. The ability of teachers in the first cycle of research results obtained by research data based on the average number based on the presentation of the first cycle, the highest score was 83.72%, the conversion value reached 3, the "Good" category, while in the second cycle the average number based on the highest score percentage was 92, 43%, conversion value reached 4, the category “Very Good”. Through collaborative assistance, the principal can improve the ability of the principal in delivering the Zoom meeting application program. Collaborative mentoring cycle I observations based on the assessment of participants the average number of classes based on the presentation of the highest score of 89.58%, when converted into a score it reached 4, with the "Very Good" category, while in the second cycle the average number was obtained based on the percentage the highest score is 92.71% when converted into a value of 4, the category "Very Good", the results of the study show that there is an increase of 3.13% in the implementation of collaborative mentoring can improve the competence of the principal in delivering the Zoom meeting application program